People centered workplaces : Fostering wellbeing and engagement - Al Arefova, Jasmina; Orel, Marko, 1986-; Hron, Michal; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2023)
The office as we know it has shifted post-covid, causing the need for organizations to reinvent the workplace, as employees started to prioritize their health. The purpose of the research is to understand the post-covid development of the workplace and what aspects contribute to a workplace that fosters an environment of wellbeing and engagement. Initial literature review laid the foundation for the qualitative research. The research was conducted in the form of semi-structured interviews with 12 experts from the UK, Switzerland, France, Belgium, and the Netherlands in the field of workplace. The results explained the development of workplace strategies post-covid and the increasing significance of creating an environment that cultivates wellbeing and engagement in the workplace. Aspects such as the physical space, organizational environment, and employee expectations are being redefined as together they impact the workplace environment, and higher emphasis is placed on wellbeing in all layers of organizations. In conclusion, organizations must embed wellbeing initiatives in the everyday environment, prioritize employees’ needs, create a variety of work settings, hold leaders responsible and support them in promoting wellbeing initiatives in the workplace, which ultimately create a universal design that supports employees’ wellbeing, helps them stay engaged, leading to happier and better performing employees.
Vedoucí práce: Marko Orel
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses